Perancangan Aplikasi Perhitungan Kebutuhan SDM Dengan ABK Kes di Unit Kerja Rekam Medis - Nina Rahmadiliyani (HB PRESS, 2023)
The Health Workload Analysis Method (ABK Kes) is a method of calculating the needs of Health Human Resources (HRD) based on the workload carried out by each type of SDMK in each health service facility in accordance with their main tasks and functions. The ABK Kes method is used for HRK planning in accordance with the capabilities of health service workers. There are 6 steps in the ABK Kes Method, including establishing Fayankes and types of SDMK, determining available work time (WKT), establishing workload components and time norms, calculating workload standards (SBK), calculating supporting task standards (STP) and supporting task factors ( FTP), and calculate the need for health human resources (HRK). The aim of the research is to design an application for calculating HR needs with ABK Kess in the medical record work unit. Computer-based workload calculation activities using Microsoft Access. Microsoft Access is an application program from Microsoft that is useful for creating, processing, and managing databases (databases).